Jaroslav Ušiak, Dávid Kollár (red.), Security Forum 2022. Conference Proceedings From the 15th Annual International Scientific Conference, February 9th, 2022, Interpolis, Banská Bystrica, Slovakia 2022, ss. 339. - Malendowicz, Paweł (Rocznik Integracji Europejskiej, 2023)
Oceny i omówienia: Jaroslav Ušiak, Dávid Kollár (red.), Security Forum 2022. Conference Proceedings From the 15th Annual International Scientific Conference, February 9th, 2022, Interpolis, Banská Bystrica, Slovakia 2022, ss. 339. (Paweł Malendowicz)